227k views
2 votes
Find an expression which represents the sum of (-3x-4y)(−3x−4y) and (x+3y)(x+3y) in simplest terms

1 Answer

5 votes

Answer:

The sum of (−3x−4y) and (x+3y) in simplest terms will be:


\left(-3x-4y\right)+\left(x+3y\right)=-2x-y

Explanation:

Given

  • (−3x−4y)
  • (x+3y)

Finding the sum of (−3x−4y) and (x+3y)


\left(-3x-4y\right)+\left(x+3y\right)


=-3x-4y+x+3y


=-3x+x-4y+3y


=-2x-4y+3y


=-2x-y

Therefore, the sum of (−3x−4y) and (x+3y) in simplest terms will be:


\left(-3x-4y\right)+\left(x+3y\right)=-2x-y

User Nightstand
by
4.9k points